Identification of Candida species in the clinical laboratory : a review of conventional, commercial, and molecular techniques - Neppelenbroek, K. H. (2014)
In healthy individuals, Candida species are considered commensal yeasts of the oral cavity. However, these microorganisms can also act as opportunist pathogens, being the so-called non-albicans Candida species increasingly recognized as important agents of human infection. A number of surveys have documented increased rates of C. glabrata, C. tropicalis, C. guilliermondii, C. dubliniensis, C. parapsilosis and C. krusei in local and systemic fungal infections. Some of these species are resistant to antifungal agents. Consequently, rapid and correct identification of species can play an important role in the management of candidiasis. Conventional methods for identification of Candida species are based on morphological and physiological attributes. However, the accurate identification of all isolates from clinical samples is often complex and time-consuming. Hence, a number of both manual and automated rapid commercial systems for the identification of these organisms have been developed, some of which may have significant problems of sensitivity. In order to overcome these limitations, newer molecular typing techniques have been developed, which allow accurate and rapid identification of Candida species. This paper reviewed the current state of identification methods for yeasts, particularly concerning Candida spp. Non-commercially and rapid commercial phenotypic methods, as well as serotyping, biotyping, and molecular typing methods are described. In addition, future directions for the identification of Candida species are also discussed.